Society – social factor of satisfaction human needs - Buyan, Ivan (Psyhology & society, 2019)
Quality of life, longevity, healthy content of material welfare, spiritual development – the highest value, constant and the most important problems which society must solve. Nature of the Universe, its inorganic component, flora and fauna not only created all the material preconditions for the full, complex satisfaction of biological and spiritual needs of each person but firstly, combined types of human needs with existing in nature minerals, proteins, fats, carbohydrates, vitamins; secondly, formed in the human body indicators (motor apparatus, brain, nervous system, biological energy) thanks to the existence of which wise human can produce the necessary items to meet the needs and services. Nature also determined that the human is able to successfully interact with it only united in society with others, completing the division of labor involving physical and spiritual abilities, creativity. An important requirement of nature – a compulsory combination of labor for the production of consumer goods and means of production itself. Instead, society – qualitatively different than nature, human needs satisfaction factor. It is the social environment, a set of economic (now mostly market), political, legal, etc. living conditions of the population. The main acting objects of socio-economic system is the power, owners of the means of production (employers) who are called to implement measures to enable the full satisfaction of human needs. The public generally interacts with nature to produce items and services, develops a system of relationships between people on the production, distribution, exchange, appropriation and consumption of material and spiritual wealth. In the last segment of everyday life there are both achievements and violence, famine, war, repression, state-oligarchic larceny, robbery of the population, half-famine concerning absolute majority of the population, and from there diseases, disability and premature mortality.